Análisis jurídico de la falta de legitimación activa, en la demanda de impugnación de reconocimiento voluntario paternidad - Benalcázar Ramón, Mayra Alejandra (2018)
This titling work brings to a close the judgment brought in the Third Court of Family, Woman, Childhood and Adolescence, signed with the Nro. 07953 - 2014 - 1845, initiated in the year 2014, the defendant is summoned, the exam is practiced of DNA, however; over the months this process was delayed, and there was the publication of Resolution 05-2014, in Registry No. 346, where the lack of procedural speed in the trials is well known as it was sentenced in 2015 , being that for the cases of minors should be given as soon as possible; as well as it was necessary to analyze in this case the acquiescence of the demanded one to solve, being that the judge pronounces itself with the lack of legitimation of the actor, reason why the aforementioned subject arises; where the objectives are one general and two particular; in the second chapter is the core part of the investigation, which is composed of the determination of paternity, the types of challenge both recognition and paternity, the requirements for it; besides the solemnities, the vices, the characteristics; a differentiation between these two, as well as the act of recognition itself; and, the principles that regulate the rights of minors such as filiation, identity, the best interests of the child, among which are also considered the rights that are thought to have been violated; also the theoretical bases of the investigation, when there is the nullity of the act, when it has the irrevocable character, which is the absence of the biological link between the parties; adding to the above is the basis of legal bases such as the Constitution of the Republic of Ecuador, the Civil Code, the Code of Childhood and Adolescence; doing comparative law, the scope of the identity right was compared with countries like Argentina and Uruguay; who relate to the law on the principle of identity, and its scope that in law according to these refers to the biological truth and the filiation of the child in litigation, in addition to the Convention of the Child; in the third chapter is the methodological procedure of the titling work, methods, type of research, and techniques; and concluding that the challenge of recognition is the right that belongs to the father who recognized the minor while the challenge of paternity to the daughter, his mother or a third party who has an interest in it, but for this was put in analysis as It should have proceeded in this case, where the initial demand existed, that is, it existed in the consent of the mother to have her surname removed, so that the defendant could have acted differently. recognized